2013
DOI: 10.1080/03057925.2013.841468
|View full text |Cite
|
Sign up to set email alerts
|

Comparing cultural differences in two quality measures in Chinese kindergartens: the Early Childhood Environment Rating Scale-Revised and the Kindergarten Quality Rating System

Abstract: This study examined the degrees of congruence between two early childhood evaluation systems on various quality concepts: the Early Childhood Environment Rating Scale-Revised (ECERS-R) and Zhejiang's Kindergarten Quality Rating System (KQRS). Analysis of variance and post hoc least significant difference tests were employed to show the extent to which the ECERS-R ratings predict a kindergarten's placement on the KQRS. Results found two quality dimensions (Language-reasoning and Interaction) that did not distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 20 publications
0
25
1
Order By: Relevance
“…Male ECTs were not expected to look after children under two years age, under the social construction of caring as 'women's work' in Chinese culture (Hou and Zhang 2009). There was also a tendency that the pedagogical aspects of ECEC were addressed with older children in Chinese kindergartens (Hu 2015), and in these centres there was little or no separation of responsibilities between male and female ECTs. This division of care and education in ECEC is believed by Western scholars to be demonstrating artificial and narrow perspectives on teaching and learning tasks, and there is a risk of failure to provide children with coherent and comprehensive ECEC programs (Warin 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Male ECTs were not expected to look after children under two years age, under the social construction of caring as 'women's work' in Chinese culture (Hou and Zhang 2009). There was also a tendency that the pedagogical aspects of ECEC were addressed with older children in Chinese kindergartens (Hu 2015), and in these centres there was little or no separation of responsibilities between male and female ECTs. This division of care and education in ECEC is believed by Western scholars to be demonstrating artificial and narrow perspectives on teaching and learning tasks, and there is a risk of failure to provide children with coherent and comprehensive ECEC programs (Warin 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This line of inquiry is critical to influencing the global promotion of inclusive education and services. In addition, considering the unique contextual features of Chinese kindergartens, such as a large class size and use of group teaching as a main curricular and instructional approach (Hu, 2014;Li, Hu, Pan, Qin, & Fan, 2014), the impact of these contextual features on engagement and interaction of children with disabilities become critical features for researchers to investigate.…”
Section: What Previous Findings Indicate About Children's Level Of Enmentioning
confidence: 99%
“…Hu examined the degrees of congruence between two early childhood evaluation systems on various quality concepts: The Early Childhood Environment Rating Scale-Revised (ECERS-R) and Zhejiang's Kindergarten Quality Rating System (KQRS). Analysis of variance and post hoc least significant difference tests were employed to show the extent to which the ECERS-R ratings predict a kindergarten's placement on the KQRS (Hu, 2015). Based on the observation of 180 early childhood classrooms using the Classroom Assessment Scoring System (CLASS), Hu et al found Chinese teachers scored lower on instruction support quality compared to international colleagues.…”
Section: Literature Reviewmentioning
confidence: 99%